2013
DOI: 10.1093/annonc/mds247
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of metabolic tumor volume measured by 18F-FDG PET/CT in advanced-stage squamous cell carcinoma of the larynx and hypopharynx

Abstract: Pretreatment MTV is an independent prognostic factor in patients with locoregionally advanced squamous cell carcinoma of the larynx and hypopharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…Either MTV (2,(15)(16)(17) or TLG (18) was measured in 5 studies, and both were measured in 8 studies (8,(19)(20)(21)(22)(23)(24)(25). The VOI was defined as the tumor (2,8,(17)(18)(19)(20)(21)(22)(23) or tumor plus metastatic lymph nodes (LNs) (15,16,24,25). Three threshold methods were adapted to segment VOIs.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Either MTV (2,(15)(16)(17) or TLG (18) was measured in 5 studies, and both were measured in 8 studies (8,(19)(20)(21)(22)(23)(24)(25). The VOI was defined as the tumor (2,8,(17)(18)(19)(20)(21)(22)(23) or tumor plus metastatic lymph nodes (LNs) (15,16,24,25). Three threshold methods were adapted to segment VOIs.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three threshold methods were adapted to segment VOIs. A fixed SUV of 2.5 (2,8,(15)(16)(17)(18)(19)22) or 3.0 (23) was used in 9 studies. The gradient segmentation method was applied in 1 study (20), and a percentage of SUVmax (30%, 42%, or 50%) was used in 3 studies (21,24,25).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…MTV 2.5 was still analyzed as significant determinant in predicting disease-free survival in resected pancreatic cancer (Table 4, and Figure 3). There have been several studies evaluating the oncologic significance of MTV 2.5 and TLG in lung cancer, 33 head and neck cancer, 34,35 esophageal cancer, 36 ovarian cancer, 37 osteosarcoma, 38 and colorectal cancer. 39,40 Several previous studies have showed the efficacy of MTV2.5 in predicting oncologic outcomes in various cancers.…”
Section: Discussionmentioning
confidence: 99%